DESIGN OF BREAKWATER AS A PROTECTION RECLAMATION ISLAND ON SEMARANG â DEMAK TOLL ROAD WORKS - Adhani, Ariz
The Semarang-Demak toll road is one of the strategic projects listed in the 2020-2024 National Medium-Term Development Plan (RPJMN). This toll road was built to serve the high mobility of the North Coast of Java (Pantura). Part of the Semarang-Demak toll road section passes through the reclamation area which requires a coastal protection structure. This final project covers breakwater planning as protection for reclamation islands requiring hydrodynamic analysis of the coast. Hydrodynamic analysis which includes analysis of water level, wave, velocity, and current direction was carried out using Delft3D software. Wave setup and wave runup are the calculation of the dimensions of the breakwater. The author designed the Breakwater building at the location of this study using the planning parameters of the breakwater building in this paper using various guidelines including the shore protection manual, and SNI 8460-2017. The breakwater design in this final project has the dimensions of a breakwater height of 8 m, a lighthouse width of 2.8 m, the main protection layer of 1.84 m, and the second layer of protection is 1 m. The main material of the breakwater layer is tetrapod with a weight of 1.6 tons, the second layer is crushed stone weighing 200 kg, and the core layer is crushed stone weighing 10 kg. The total volume of buildings planned for this study area is 601,988 m3 with a planned budget of around Rp. 310,9 billion.